Efficacy and safety of combining a thiazide diuretic with a loop diuretic in decompensated heart failure: A systematic review and meta-analysis - Rodrigo Bessa; Otavio C. Martins; Isadora Mamede; Anne E.O. Franchini; Marcel C.F. Santos (International Journal of Cardiology: Heart & Vasculature)
Background: Acute decompensated heart failure (ADHF) often presents as congestion, typically treated with intravenous loop diuretics. However, prolonged use of this therapy may lead to resistance which can be overcome by adding a thiazide diuretic. Less is known about the safety of this combination. Objectives: We aimed to perform a meta-analysis comparing the efficacy and safety of a loop monotherapy versus a combination of loop and thiazide. Methods: We systematically searched PubMed, Embase, and Cochrane for randomized controlled trials (RCTs) and observational studies comparing patients with ADHF using only loop diuretics to those using a thiazide adjuvant therapy. Statistical analyses were conducted using R software (v 4.3.2) and a random-effects model was employed for all outcomes. Results: Four RCTs and six observational studies, with a total of 17,325 patients, met our inclusion criteria. There was no significant difference in all-cause mortality (RR 1.77; p = 0.094) between the groups. Overall, individuals receiving the diuretic combination experienced greater weight loss (Mean Difference −0.58; p = 0.028) but also had a higher incidence of hyponatremia (RR 2.15; p < 0.001) and hypokalemia (RR 2.27; p < 0.001). There was no significant difference in all hospital readmissions, length of hospital stay, diuresis, and creatinine change. Conclusions: Despite the observed weight loss, combined therapy did not lead to reduction in mortality, hospitalization duration, or hospital readmission, and also increased risk of hyponatremia and hypokalemia. Routine use of combined therapy is not advisable, given the substantial evidence of associated risks outweighing potential benefits.